A MODEL OF RELIGIOUS LIFE BASED ON THE MADINAH CHARTER FOR CHARACTER FORMATION OF STUDENTS IN MEDAN CITY - Alkausar Saragih, Nelvitia Purba, Rahmadi Ali (LP2M Universitas Muslim Nusantara Al Washliyah, 2026)
This study aims to determine interfaith harmony in the Islamic version, as a religion that is a blessing for all creation. The Medina Charter, consisting of 47 articles, laid the foundations for the life of religious communities in a pluralistic and diverse nation, encompassing both ethnicity and religion. The Medina Charter specifically stipulates